SM-ND ISOTOPIC SYSTEM IN GARNET MEGACRYSTS FROM THE UDACHNAYA KIMBERLITE PIPE (YAKUTIA) AND PETROGENESIS OF KIMBERLITES - Agashev A.M.; Pokhilenko N.P.; Mal'kovets V.G.; Sobolev N.V. (My University, 2006)
The discrete xenocryst association is a significant component of kimberlites. Most kimberlite bodies comprise one or several minerals of the following association: olivine ± garnet ± clinopyroxene ± orthopyroxene ± ilmenite ± phlogopite ± zircon. Ilmenite in this association is characterized by the Cr2O3 and Al2O3 admixture, while garnet is characterized by a high amount of TiO2 admixture, depending both on the medium composition and the formation temperature. The xenocryst association is usually subdivided into megacrysts (>1 cm) and macrocrysts (<1 cm). The low-Cr megacryst association is supposed to be the product of crystallization of the OIB-type asthenospheric magma at high PT values in lower horizons of the lithospheric mantle.
Keywords: garnet megacrysts; kimberlites; Udachnaya kimberlite pipe